Epidemiological profile and functional status of patients with Duchenne muscular dystrophy seen in physiotherapy clinics in the city of Aracaju - Freitas, Mayanna Machado (2013)
The Duchenne Muscular Dystrophy is most common and the most severe of the muscular dystrophies, where the signals and symptoms are more severe with faster evolution, death can occur around the 2nd or 3nd decade of life. Currently, the incidence is estimated at around one for each three thousand five hundred male births. To determine the prevalence of Duchenne Muscular Dystrophy in the city of Aracaju-SE, and to characterize the functional profile presented by these patients. The study included all patients with Duchenne Muscular Dystrophy, assisted at the physiotherapy clinics in this city. The data were collected from January to April 2011; initially in the medical records of each patient, and subsequently, the identified patients were submitted for clinical and epidemiological evaluation. Among the functional limitations found in most patients studied, mainly includes the involvement of the lower limbs. The patients evaluated in Aracaju showed moderate functional impairment to perform activities of daily living, characterizing the need to implement actions and private and public policies aimed at the improvement of life quality of these patients.